The implications of conditionality social assistance programmes - Dornan, P; Porter, C (Edward Elgar Publishing, 2013)
Social protection measures as the cornerstone of social policy in low- income countries are riding high on the international development policy agenda. This has led to a rapid increase in the number of state-led schemes aimed at alleviating chronic poverty and vulnerability in lower- income countries since the turn of the twenty-first century with a growing focus on conditionality. International policy attention to social protection is illustrated by the ongoing UN Social Protection Floor initiative, launched in 2009, focusing attention on social protection through the UN system (ILO and OECD 2011). The focus was sharpened by the recent global financial downturn (World Bank 2009a), with social protection positioned as a key tool to help countries and households both cope with the crisis and to deliver more ‘inclusive development’ (European University Institute and European Commission 2010). A key policy message is that countries with established social protection systems in place were able to react more quickly to the crisis (World Bank 2010). The Bank makes use of ‘3P’ framework of Prevention, Promotion and Protection common in discussions about social protection (World Bank 2010), though it is perhaps worth noting that others have sought to introduce a ‘transformative’ element into the framework (see Devereux and Sabates-Wheeler 2004) to emphasize the potential of effective social protection in empowering marginalized groups. There is therefore an increasing and welcome recognition that one-off or patchwork solutions to social protection challenges are inadequate, and that more comprehensive systems are needed.